PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN PADA PERCETAKAN REGISTER PRINT - Fitriyani, Nida; Supriyanto; Kurniawan, Dody; Siahaan, Matdio; Anas, Haryudi (SINERGI : Jurnal Riset Ilmiah, 2025)
Human resources are one of the key factors in determining the operational success of an organization or company. This study aims to determine the influence of work environment and individual characteristics on employee performance. This research uses a descriptive quantitative approach with the assistance of SPSS software. The sampling technique used is saturated sampling, in which the entire population is used as the sample, consisting of 50 employees. The results of the study show that partially, the work environment has a significant influence on employee performance. Meanwhile, individual characteristics do not have a significant effect on performance. Simultaneously, the work environment and individual characteristics can influence employee performance; however, the most dominant influence comes from the work environment. Therefore, companies need to pay more attention to creating a conducive work environment in order to optimize employee performance.